Vitamin A nutritional status in high- and low-income postpartum women and its effect on colostrum and the requirements of the term newborn - Cristiane Santos Sânzio Gurgel; Evellyn C. Grilo; Larissa Q. Lira; Débora G.F. Assunção; Priscila G. Oliveira; Larisse R.M. de Melo; Silvia V. de Medeiros; Luanna C. Pessanha; Roberto Dimenstein; Clélia O. Lyra (Elsevier, 2018)
Objective: To evaluate the vitamin A status in serum and colostrum of postpartum women with different socioeconomic status, comparing the colostrum retinol supply with the vitamin A requirement of the newborn. Methods: Cross-sectional study conducted with 424 postpartum women. Vitamin A maternal dietary intake was estimated using a food frequency questionnaire. Colostrum and serum retinol levels were measured by high performance liquid chromatography (HPLC). Serum retinol concentrations <20 μg/dL were indicative of vitamin A deficiency (VAD). Vitamin A levels provided by colostrum <400 μgRAE/day were considered as insufficient for term newborns. Results: The mean maternal vitamin A intake during pregnancy was 872.2 ± 639.2 μgRAE/day in low-income women and 1169.2 ± 695.2 μgRAE/day for high-income women (p < 0.005). The prevalence of vitamin A deficiency was 6.9% (n = 18) in the low-income group and 3.7% (n = 6) in the high-income group. The estimated mean retinol intake by infants of the high- and low-income mothers were 343.3 μgRAE/day (85.8% AI) and 427.2 μgRAE/day (106.8% AI), respectively. Conclusions: Serum vitamin A deficiency was considered a mild public health problem in both populations; however, newborns of low-income women were more likely to receive lower retinol levels through colostrum when compared with newborns of high-income mothers. Resumo: Objetivo: Avaliar o estado nutricional de vitamina A no soro e colostro de puérperas com diferentes condições de renda, comparando os níveis de retinol fornecido através do colostro com a necessidade de vitamina A do recém-nascido. Métodos: Estudo transversal com 424 mulheres pós-parto. A ingestão de vitamina A dietética pelas mães foi estimada através de um questionário de frequência do consumo alimentar. Os níveis retinol no soro e colostro foram quantificados por cromatografia líquida de alta eficiência (CLAE). Concentrações de retinol <20 μg/dL no soro foram indicativas de vitamin A deficiency. Os níveis de vitamina A fornecidas pelo colostro < 400 μg/RAE/dia foram considerados insuficientes para os recém-nascidos a termo. Resultados: A ingestão média de vitamina A das mães durante a gravidez foi de 872,2 ± 639,2 μgRAE/dia em mulheres de baixa renda e 1169,2 ± 695,2 μgRAE/dia em mulheres de alta renda (p < 0,005). A prevalência de vitamin A deficiency foi de 6,9% (n = 18) no grupo de baixa renda e de 3,7% (n = 6) no grupo de alta renda. A estimativa dos valores médios de ingestão de retinol por lactentes de mães de baixa e alta renda foi de 343,3 μg/RAE/dia (85,8% AI) e 427,2 μg/RAE/dia (106,8% AI), respectivamente. Conclusões: A vitamin A deficiency no soro foi prevalente em ambas as populações, entretanto, recém-nascidos de mães de baixa renda foram mais propensos a receberem níveis inferiores de retinol no colostro em comparação com recém-nascidos de mães de alta renda. Keywords: Vitamin A, Colostrum, Postpartum women, High-income, Low-income, Newborn, Palavras-chave: Vitamina A, Colostro, Pós-parto, Alta renda, Baixa renda, Recém-nascido